Standalone Report, Assurance Report, GRI Reporting Framework dan Kualitas Pengungkapan Sustainability Report - Huda Trihatmoko; Sri Ningsih; Muhammad Raihan Mubaraq (Universitas Pamulang, 2020)
The purpose of this study was to examine the effect of a standalone report, assurance report, and GRI reporting framework on the quality of sustainability report disclosure in companies listed on the Indonesia Stock Exchange in 2016-2018. Measurement of the quality index of the sustainability report disclosure in identifying the item or content of the analysis uses the total quality score of the sustainability report disclosure for each company compared to the absolute maximum disclosure score. The standalone report, assurance report, and GRI reporting framework measurement uses a dummy: 1 if it owns the component and 0 if it does not. The sample of this research is 145 companies selected by purposive sampling method. The results of this study indicate that the standalone report and the assurance report do not affect. Still, the GRI reporting framework has a significant positive effect on the quality of sustainability report disclosureABSTRAKTujuan penelitian ini adalah untuk menguji pengaruh standalone report, assurance report dan GRI reporting framework terhadap kualitas pengungkapan sustainability report pada perusahaan yang terdaftar di Bursa Efek Indonesia tahun 2016-2018. Pengukuran indeks kualitas pengungkapan sustainability report dalam mengidentifikasi item atau isi analisis menggunakan total skor kualitas pengungkapan sustainability report untuk masing-masing perusahaan dibandingkan dengan total skor pengungkapan maksimum. Pengukuran standalone report, assurance report dan GRI reporting framework menggunakan dummy, yaitu 1 jika perusahaan memiliki komponen, dan 0 jika tidak. Sampel penelitian ini adalah 145 perusahaan yang dipilih dengan metode purposive sampling. Hasil penelitian ini menunjukkan bahwa standalone report dan assurance report tidak berpengaruh, namun GRI reporting framework berpengaruh positif terhadap kualitas pengungkapan sustainability report